Death, graveyards and funerary architecture in Islam - Omer, Spahic (A.S.Nordeen, 2008)
This book aims to cast some light on the theme of Muslim funerary architecture, thus attempting to render the answers on some crucial questions often asked about it. The book focuses on the origins, roles and significance of funerary architecture in Islamic civilization. It follows that discussing the plans and structural designs of funerary structures is not a focus in the book. The topics discussed are divided into five chapters entitled: Death in Islam, Visiting Graves; The Prophet Muhammad’s Grave; The Birth of Funerary Architecture in Islamic Civilization; The Reasons for the Institution and Proliferation of Funerary Architecture in Islamic Civilizations.